2011
DOI: 10.1007/s12598-011-0428-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and fracture behaviors on 6061 aluminum alloy under shear stress state

Abstract: The mechanical properties and fracture behaviors of 6061 aluminum alloy were investigated by the tensile shear tests and in-situ tensile shear tests with tensile shear specimen devised. The results indicate that many slip bands parallel to tensile direction are produced on the surfaces of the specimens. With shear strain rates increasing, the shear yield stress and shear ultimate stress of 6061 aluminum alloy remain constant basically, but the shear fracture strain decreases obviously. The shear strain rates h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Based on Table 3, it can be seen that the highly ductile 1060-H112 aluminum alloy projectile did not fragment, fall off, or break at higher initial velocities compared to higher strength aluminum alloy materials such as 6061-T6511H, 7A04, and 2A12. 1,5,7,19 The recovered projectile at the end of the test showed little change in the body mass. The experimental phenomenon verifies the conclusion given by Teng et al 20 based on numerical simulation results that upsetting and petal cracking occurred in highly ductile metal projectiles.…”
Section: Taylor Impact Testmentioning
confidence: 94%
“…Based on Table 3, it can be seen that the highly ductile 1060-H112 aluminum alloy projectile did not fragment, fall off, or break at higher initial velocities compared to higher strength aluminum alloy materials such as 6061-T6511H, 7A04, and 2A12. 1,5,7,19 The recovered projectile at the end of the test showed little change in the body mass. The experimental phenomenon verifies the conclusion given by Teng et al 20 based on numerical simulation results that upsetting and petal cracking occurred in highly ductile metal projectiles.…”
Section: Taylor Impact Testmentioning
confidence: 94%
“…Recently, there have been active studies on fracture mechanisms in different stress states, and emphasis have been laid on the relation between fracture criterion and different fracture mechanisms [11][12][13][14][15][16][17][18]. For instance, Tang and Wang [19] showed that the criterion based on only brittle and ductile fracture is not sufficient for the prediction of all fracture modes.…”
Section: Introductionmentioning
confidence: 99%
“…Clinching process, a mechanical joining method, has been widely used in the aerospace, automobile industry, railway transportation and furniture industries due to its advantages of the connection of sheets [1][2][3][4][5]. Although the patent of the clinching was granted in 19 century, the clinching technology was not used in the industries.…”
Section: Introductionmentioning
confidence: 99%